Korelasi Metode Resitasi Terhadap Hasil Belajar Al-Quran Hadis di MTs Negeri 1 Pangkalpinang - Karyono, Karyono; Pritama, Annisa (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The objective of this study is to find out what factors influence the learning outcome of the student and how much the reading outcome impacts the learning outcomes of the pupil on the teaching of the Quran in the state of 1st Grade VII in the teaching year 2021-2022. This research uses a type of quantitative survey. The total population in this study was 213 pupils. As for the type of sampling used, the technique is random sampling, so there are 106 pupils who are sampled. Data collection techniques using Angket and documentation Then the data analysis technique in this research uses normality, linearity, and simple regression with the help of SPSS 26 for Windows. There is a positive and significant influence between the variables of the method of recitation on learning outcomes. There is a simultaneous influence of the method of recitation on the learning outcome of the students on the subjects of the Qur'an hadith of grade VII in the state of MTs 1 based proof with F count > F table (37,965 > 3,96) and sig (0,063 > 0,05) means H0 rejected and H1 accepted. The regression with the formula Y=a + bx can be known through the output table above, where the constant values are 92,865 and the values for the variable method recitation are 0.091, so the equation is: Y = 92,865 + 0,091 X. The determination coefficient R2 0.033 x 100 = 3.3% of this variable X has an influence on the learning outcome, which is shown above, and the rest is influenced by variables that do not participate in the assessment. The limitations of this study are that it only investigates one method against the student's learning outcomes and does not investigate other factors, of which of course many other factors can influence the learning outcome, such as learning motivation, parents' attention, interest in learning, or other free variables.